2018
DOI: 10.1111/scs.12585
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐validation of the Self‐care Ability Scale for Elderly (SASE) in a sample of Italian older adults

Abstract: The assessment of self-care among older adults is important as it permits the tailoring of educational interventions directed to prevent health deterioration and contrast the effects of ageing. The Self-care Ability Scale for the Elderly (SASE) was developed to assess the perceived self-care ability in older adults. Its psychometric properties were tested only in Scandinavian countries and China. This research was a cross-validation of the SASE on 402 Italian adults aged 65 and older recruited in hospitals, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 37 publications
4
11
1
Order By: Relevance
“…20) The original Swedish version of the SASE has been translated to Chinese, Italian, Norwegian, and Persian. [20][21][22][23][24] The culturally adapted versions are reliable, valid, and frequently used tools to assess self-care ability in older adults. Our study translated and adapted the SASE into Turkish according to internationally accepted guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…20) The original Swedish version of the SASE has been translated to Chinese, Italian, Norwegian, and Persian. [20][21][22][23][24] The culturally adapted versions are reliable, valid, and frequently used tools to assess self-care ability in older adults. Our study translated and adapted the SASE into Turkish according to internationally accepted guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…The original Swedish version showed Cronbach’s alpha values of 0.68 and 0.88 in older patients and community-dwelling older adults, respectively. 20 ) The Cronbach’s alpha value for the Italian version ranged from 0.72 to 0.90, 23 ) while the values for the Chinese, Norwegian, and Persian versions were 0.89, 0.85, and 0.73, respectively. 21 , 22 , 24 ) The results demonstrated the acceptable to high consistency of the SASE in all cultures, including Turkey.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed that chronic diseases were associated significantly with perceived health status or subjective health, as well as different factors were correlated with self-reported health for different age groups. According to study (18) showed that the number of chronic diseases such as hypertension was the strongest predictor of selfrated health among elderly people aged 70 to 79 .…”
Section: Discussionmentioning
confidence: 99%